Controlador desacoplado para manipulador robótico articulado com três graus de liberdade - Lopes, Igor Cabral Machado (2020)
This work proposes a control technique applied to an articulated robotic manipulator, classified in the literature as anthropomorphic (RRR), which is formed by three rotary joints, three degrees of freedom, and spatial movement. Articulated manipulators (RRR) have a great freedom of movement inside their workspace and are a type of manipulator widely used. Two control strategies will be implemented, the first is the variable structure model reference adaptive control, and the second one is a linear proportional derivative controller. Both controllers proposed will use an inversion technique to decouple the dynamic of each joint of the RRR manipulator, resulting in an independent controller for each joint. In the end, simulated results will be presented, and some analyzes about them will be made.